PENGARUH PENDAPATAN ORANGTUA DAN PENGETAHUAN EKONOMI TERHADAP PERILAKU KONSUMSI SISWA SMA NEGERI 1 JAWAI - Joharelita, Masita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThe problem in this research is â€œwhether there is influence of parental income and economy knowledge on consumption behaviorÂ of SMAN 1 Jawai?â€. The research method used is descriptive quantitative method with interrelationship studies, with the research sample is 59 students. Data is collected by techniques indirectly communication (kuisioner) and techniques direct communication (interview). Of the results data processing with program assistance spss 16.0 version for variables (x1) of variable (y) obtained value thitung (1,367)<ttabel (2,003), the partial parental income does not affect on student's consumption behavior.Â For variables ( x2) of variable ( y ) obtained value thitung (2,070)>ttabel (2,003), and the probability t (sig.) is (0,043<0,05), then as partial economiy knowledge have a positive impact and significant on students consumption behavior. The result of the regression analysis of influence parental income and economy knowledge on the consumption behavior is Y= 49,615+(-0,345)X1+0,638X2 . Next analysis F test obtained value Fhitung (2,457)< Ftabel (3,162) and having r square value very low is 8,1%. Thus simultaneously parental income and economy knowledge do not affect in significant impact on students consumption behavior of SMAN 1 Jawai.Keywords: Parent Income, Economy Knowledge, Consumption BehaviorÂ